L’archéogéographie : pour une reconnaissance du passé dans l’espace - Dominique Guillaud (EchoGéo)
This paper confronts the local representations of the past territories to their scientific reconstitutions by archaeologists, leading to yet another definition of “archaeogeography”. This approach, experimented in the Pasemah region, in the highlands of Sumatra, shows the complementary nature of data supplied by the oral tradition and by archaeology concerning the history of settlement. It also provides important landmarks for the understanding of present-day territoriality, which is always deeply rooted in time.